Structure and function of carbohydrates - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Properties of carbohydrates and their complexity, Carbohydrate energy role, Carbohydrate structural role, Glycosaminoglycans & proteoglycans, Carbohydrate recognition role
Reviewed at 2022/11/27